2020
DOI: 10.1038/s41598-020-73962-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel severity score to predict inpatient mortality in COVID-19 patients

Abstract: COVID-19 is commonly mild and self-limiting, but in a considerable portion of patients the disease is severe and fatal. Determining which patients are at high risk of severe illness or mortality is essential for appropriate clinical decision making. We propose a novel severity score specifically for COVID-19 to help predict disease severity and mortality. 4711 patients with confirmed SARS-CoV-2 infection were included. We derived a risk model using the first half of the cohort (n = 2355 patients) by logistic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 18 publications
9
100
3
1
Order By: Relevance
“…However, the study did not analyze survival and death among patients with a confirmed COVID-19 diagnosis. In addition to studies attempting to predict death in patients with COVID-19, other studies have focused on severity index to predict severe or critical cases [ 10 , 28 - 31 ]. More recently, a machine learning–based warning system for mortality risk prediction of patients with COVID-19 was reported, and timely risk stratification using multiple laboratory and clinical factors was improved [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not analyze survival and death among patients with a confirmed COVID-19 diagnosis. In addition to studies attempting to predict death in patients with COVID-19, other studies have focused on severity index to predict severe or critical cases [ 10 , 28 - 31 ]. More recently, a machine learning–based warning system for mortality risk prediction of patients with COVID-19 was reported, and timely risk stratification using multiple laboratory and clinical factors was improved [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary endpoints were determined as improvements in SpO 2 and vital signs as well as the general wellbeing of the patient. Severity score was calculated based on the scoring system suggested by Altschul et al for prediction of inpatient mortality in COVID-19 patients [21]. Based on this scoring system, the higher the score of the patient, the higher the odds of inpatient mortality.…”
Section: Measurements and Statistical Analysismentioning
confidence: 99%
“…Additional prognostic information provided with the CT severity index means it can be used as an important metric for a triage system to determine who needs to be admitted/home quarantined and so on. [ 16 ] Easy scalability with high throughput, the possibility of remote diagnosis by leveraging teleradiology facilities mean that the HRCT chest is a very useful tool for initial diagnosis. Additional information for other causes of breathlessness (e.g., cardiomegaly/pleural effusions/pulmonary edema and even malignancies) may also be available.…”
Section: Discussionmentioning
confidence: 99%